2020
DOI: 10.3390/jcm9030848
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of Sustained Ventricular Arrhythmia Recurrence After Acute Myocarditis

Abstract: Acute myocarditis is associated with cardiac arrhythmia in 25% of cases; a third of these arrhythmias are ventricular tachycardia (VT) or ventricular fibrillation (VF). The implantation of a cardiac defibrillator (ICD) following sustained ventricular arrhythmia remains controversial in these patients. We sought to assess the risk of major arrhythmic ventricular events (MAEs) over time in patients implanted with an ICD following sustained VT/VF in the acute phase of myocarditis compared to those implanted for V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…As demonstrated by Peretto et al, these anatomopathological and arrhythmogenic differences clinically manifest themselves with two different arrhythmic patterns: polymorphic and irregular ventricular arrhythmias are more common during the active inflammatory phase, whereas monomorphic and regular ventricular arrhythmias, suggesting a static and “cold” substrate, are associated with healed myocarditis. Similarly, a French study found that ventricular fibrillation was the most common initial ventricular arrhythmia in acute myocarditis setting (58%), that ventricular tachycardia was the most common in myocarditis sequelae (78%), and that cardiorespiratory arrest was twice as frequent in the course of acute myocarditis (68 versus 30%) ( 75 ).…”
Section: Potential Mechanisms Of Arrhythmia In Myocarditismentioning
confidence: 98%
See 1 more Smart Citation
“…As demonstrated by Peretto et al, these anatomopathological and arrhythmogenic differences clinically manifest themselves with two different arrhythmic patterns: polymorphic and irregular ventricular arrhythmias are more common during the active inflammatory phase, whereas monomorphic and regular ventricular arrhythmias, suggesting a static and “cold” substrate, are associated with healed myocarditis. Similarly, a French study found that ventricular fibrillation was the most common initial ventricular arrhythmia in acute myocarditis setting (58%), that ventricular tachycardia was the most common in myocarditis sequelae (78%), and that cardiorespiratory arrest was twice as frequent in the course of acute myocarditis (68 versus 30%) ( 75 ).…”
Section: Potential Mechanisms Of Arrhythmia In Myocarditismentioning
confidence: 98%
“…Indeed, data from the Multicenter Lombardy Registry showed that patients with complex ventricular arrhythmias at presentation were at higher risk of worse long-term outcomes than uncomplicated myocarditis cases that had, instead, benign long-term prognosis and low risk of subsequent arrhythmic events and left ventricular systolic dysfunction ( 30 ). Similarly, a French study ( 75 ) showed that patients presenting with ventricular tachycardia or ventricular fibrillation in the acute phase of myocarditis who had received ICD implantation early for secondary prevention had a very high risk (39%) of recurrence of major arrhythmic ventricular events (MAEs) over a median follow-up period of 3 years. In addition, an alarming 80% of patients in a study subgroup who preferred not to have ICD implantation experienced an MAE over time.…”
Section: Long-term Prognosis and Implantable Defibrillator Indication...mentioning
confidence: 99%
“…In 2022, Sharifrazi and his research fellows proposed the concept of computer-aided diagnosis to try and address the inaccuracy in the diagnosis of myocarditis [ 4 ]. Moreover, little is known about the clinical progression of the disease and further studies are required in this area [ 31 , 32 ]. American Heart Association stated that timely diagnosis and treatment are crucial to the prognosis of patients with fulminant myocarditis in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of VT or sudden cardiac death following viral myocarditis can be as high as 50% in adults, likely from persistent inflammation or postinflammatory myocardial scar, highlighting the importance of follow‐up. 18 Cases of arrhythmias and sudden cardiac death have also been reported in children following myocarditis, including in patients with normal ventricular function. However, there is no good estimate of the risk, likely because of the rarity of events.…”
Section: Discussionmentioning
confidence: 99%